Treatment of uveitis and scleritis patients in Malaysia - Sieng Teng Seow; Iqbal Tajunisah; Fei Yee Lee; Pooi Wah Lott; Sagili Chandrasekhara Reddy (International Journal of Ophthalmology, 2024)
AIM: To determine the common causes and visual outcome after treatment among uveitis and scleritis patients. METHODS: This is a retrospective cohort observational study. All consecutive clinical records of patients with newly diagnosed uveitis and scleritis over a 4-year period, from Jan. 1, 2017 to Dec. 31, 2020, were analysed. Data was collected at the presentation and included a follow-up period of one year. RESULTS: A total of 288 patients were recruited during the study period. Anterior uveitis was the most common anatomical diagnosis (50.0%) followed by panuveitis (25.0%), scleritis (13.5%), posterior uveitis (6.9%), and intermediate uveitis (4.5%). Viral Herpes was the most common cause of infectious cases, while Vogt-Koyanagi-Harada (VKH) disease and human leucocyte antigen (HLA) B27 spondyloarthropathy were the leading causes of identifiable non-infectious cases. Majority of patients presented with unilateral, non-granulomatous uveitis with an absence of hypopyon. Anatomical locations like posterior uveitis and panuveitis, and visual acuity worse than 3/60 at presentation were the factors associated with poor visual outcomes (P<0.05). About 60% of patients had an identifiable cause for the uveitis and scleritis, with nearly equal distribution of infectious (n=85, 29.5%) and non-infectious causes (n=84, 29.2%). About 14.5% of patients were clinically blind at 1y of follow-up. The most common complication in our uveitis patients was glaucoma (47.5%), followed by cystoid macula oedema (18.9%) and cataract (13.9%). CONCLUSION: Uveitis and scleritis are important causes of ocular morbidity. They are potentially blinding diseases which can have a good outcome if diagnosed and treated early.